Advanced Computing in Electron Microscopy - Kirkland, Earl J (Springer Science + Business Media, 2010)
This book provides a summary of methods for numerical computation of high resolution conventional and scanning transmission electron microscope images. At the limits of resolution, image artifacts due to the instrument and the specimen interaction can complicate image interpretation. Image calculations can help interpret and understand high resolution information in recorded electron micrographs. This revised edition contains new sections on recent instrumental developments and updated references. It should be useful for beginning and experienced users at the advanced undergraduate or graduate level. This new edition will be a revision of the existing text, including new developments in this field since the original manuscript and updated references. Additional material will include abberration corrected instruments and confocal electron microscopy. The references and examples will be improved and expanded and some sections polished to improve ease of understanding. TOC:Introduction.- The transmission electron microscope.- Linear image approx.- Sampling and the fast fourier transform.- Calculating images of thin specimens.- Calculating images of thick specimens.- Some worked examples.- Program details.- App. A: Atomic potentials and scattering factors.- App. B: The fourier projection theorem.- App. C: Bilinear interpolation.- App. D: 3D perspective view.